TECHNIQUE OF TRANSLATION: REVIEWING THE THEORY - Maretha, Carla; Wahyuningsih, Yulia; Alrajafi, Gali (SIGEH ELT : Journal of Literature and Linguistics, 2022)
This article concerns on the translation techniques based on the emphasis of language, source and target. This article is conducted with qualitative reserch design by using library study and review of literature. This article shows that the emphasis in translation, whether source langauge or target language has suitable technique in transfering the idea of source text. This article shows that source language emphasis closely relates to word level equivalence that might be assisted by machine translation or fully exploring human capital of thinking. Meanwhile, the target language emphasis closely relates to sense of language notions which focus on readable and acceptable aspect of translation product.